Conceptual Model of Information Technology Governance in Higher Education Institution - Yanti Rosmunie, Bujang; Rosita, Mohamed Othman; Nadianatra, Musa (2022)
Information Technology (IT) is widely used in teaching, learning, and administration in higher education institutions. The managers of those institutions are more aware that IT is a strategic tool for their institutions. Therefore, Information Technology Governance (ITG) is getting more attention from the practitioner and researcher, given the need to govern IT, extending the organization's strategy and objectives into IT. ITG helps to set clear expectations, gain participation, open communications, establish accountability and provide executive management oversight. Hence, it is essential to consider ITG and its alignment with higher education institutions' business strategies. ITG has been challenging for years, and research has grown substantially. However, the research found the existence of a gap between theoretical frameworks and practices. Current ITG research primarily focuses on hard governance (structure, processes), but soft governance (behaviour, collaboration) is equally important and might be crucial to close the gap. This study aims to identify the factors contributing to ITG adoption's success in higher education institutions in Malaysia. Although yet to be tested, a study adopting the proposed framework is anticipated to enable Higher Education Institution (HEI) to improve the best practices or processes to deliver good service quality.